Average hourly earnings for salaried employees (paid a fixed salary) (SEPH), including overtime, unadjusted for seasonal variation, for selected industries classified using the North American Industry Classification System (NAICS) - Statistics Canada (Government of Canada, 2017)
This table contains 2144 series, with data for years 1991 - 2000 (not all combinations necessarily have data for all years). This table contains data described by the following dimensions (Not all combinations are available): Geography (13 items: Canada; Prince Edward Island; Nova Scotia; Newfoundland and Labrador ...), North American Industry Classification System (NAICS) (366 items: Industrial aggregate excluding unclassified businesses; Forestry; logging and support; Goods producing industries ...).